Primary Vulval Rhabdoid Tumor in an Adult: A Case Report, Immunohistochemical Profile and Literature Review - Maria A. Arafah; Muna I. Aljuboury (Case Reports in Medicine)
We report a rare case of primary vulval rhabdoid tumor in an adult. The diagnosis was confirmed using the recently emerging INI1/BAF47 immunostain. We also demonstrate the expression of ER and PR hormonal receptors by the tumor cells.